Einfluss früher Gewalterfahrungen von Frauen auf die Mutter-Kind-Beziehung: Daten von Heidelberger und Berliner Mutter-Kind-Dyaden - Neukel, Corinne; Spieß, Karen; Bertsch, Katja; Möhler, Eva; Resch, Franz; Kaess, Michael; Brunner, Romuald; Herpertz, Sabine (Der Nervenarzt, 2019)
Early life maltreatment can have severe and long-lasting consequences for the directly affected individual as well as for the next generation. Data from our research including mother-child dyads from Heidelberg and Berlin show that early life maltreatment is associated with behavioral and neural changes including personality traits and attachment style of the affected mothers that negatively affect their relationship with their child. The children of these mothers affected by early life maltreatment have an elevated risk to be maltreated and to develop mental disorders. They also show a heightened cortisol concentration and a reduced inhibition control. It seems to be of importance whether the mother has experienced early life maltreatment but is resilient, meaning that she has not developed a mental disorder (up to the time of examination) or whether in addition to the early life maltreatment she has developed a mental disorder later in life. Children of mothers with early life maltreatment and a lifetime mental disorder seem to be especially exposed to stress and show the greatest impairments and risks. Based on the existing data from our research practical and clinical implications are discussed and one possible intervention in the form of a training of mentalization competencies for parents is presented.